Insights from the 2020 Global Food Policy Report for Central Asia - Akramov, Kamiljon T. (2020)
Kamiljon Akramov GLOBAL FOOD POLICY REPORT Virtual Event--Discussion on the Implications of the 2020 Global Food Policy Report for Eurasia Co-Organized by the Eurasian Center for Food Security at Lomonosov Moscow State University, Westminster International University in Tashkent, the World Bank Group, and IFPRI MAY 27, 2020 - 02:30 PM TO 04:00 PM MSK